1988
DOI: 10.1111/j.1464-410x.1988.tb04397.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary Mediastinal Seminoma

Abstract: Two new cases of primary mediastinal seminoma are presented and 126 cases from the literature are analysed. Radiotherapy, alone or combined with surgery, is thought by some authors to be the treatment of choice and the role of chemotherapy is uncertain. We propose a classification by which it is possible to compare various therapeutic approaches and to establish their value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…After teratoma, seminoma is the second most common germ cell tumor of the mediastinum in its pure form 19, 20. However, the true incidence of seminomas has been difficult to assess due to the relatively small series of cases reported until now 21‐46. In our experience, primary mediastinal seminomas have accounted for approximately 37% of all mediastinal germ cell tumors and taken second place only to teratomas.…”
Section: Discussionmentioning
confidence: 76%
“…After teratoma, seminoma is the second most common germ cell tumor of the mediastinum in its pure form 19, 20. However, the true incidence of seminomas has been difficult to assess due to the relatively small series of cases reported until now 21‐46. In our experience, primary mediastinal seminomas have accounted for approximately 37% of all mediastinal germ cell tumors and taken second place only to teratomas.…”
Section: Discussionmentioning
confidence: 76%
“…Nonetheless, such tumors have also been described in other locations, such as the pineal gland, retroperitoneum, mediastinum, and sacral area 2‐4. Germ cell tumors arising primarily in the mediastinum are uncommon and have mostly been the subject of case reports; very few comprehensive studies on this topic have been reported in the literature 2, 4‐103. It has been estimated in some studies that extragonadal germ cell tumors account for approximately 1‐15% of mediastinal tumors in adults and approximately 25% in children 21, 59, 60, 104…”
mentioning
confidence: 99%
“…Therefore, tumors with morphological features of seminoma were termed, for instance, "seminoma-like tumor" or "seminomatous thymoma" [2,3]. In the 1970s and 1980s, the concept of primary mediastinal germ cell tumors (PMGCTs) became well established [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%